Installation Performance Evaluation Domestic Wastewater Treatment Plant in Fulfil Minister of Environment and Forestry Regulation No. 11 of 2025 - Irfan Syarifandi; Natsar Desi; Muhammad Chaerul; Erniati Erniati; A.M.Yusuf Harun; Mahmud Mahmud (Newinera Publisher, 2026)
Wastewater management domestic is aspect crucial in control pollution environment. especially in developing areas like Merauke Regency. Research This aim evaluate performance Installation Domestic Wastewater Treatment Plant ( WWTP) in Housing District Ulilin in fulfil standard quality Minister of Environment and Forestry Regulation No. 11 of 2025. Research method use approach quantitative descriptive – evaluative with design studies case. Taking sample carried out at the inlet and outlet of the IPAL during September–October 2025 using grab sampling method. with Analysis of TSS, pH, BOD₅, COD, oil and fat, NH₃-N, and total coliform parameters based on Standard Methods (APHA, 2017). The results show that characteristics influence majority exceed standard quality. especially in the parameters BOD₅ (33.4 mg/L), COD (122.5 mg/L), TSS (35.5 mg/L), oil and fat (6.15 mg/L), NH₃-N (13.1 mg/L), and total coliform (3.59×10³ MPN/100 mL). After processing. all effluent parameters fulfil standard quality with level 100% compliance Efficiency elimination show very good performance. with decline significant on BOD₅ (83.38%), COD (84.04%), TSS (49.30%), and NH₃-N (93.13%). High safety margin to standard quality show system own capacity adequate and resilient reserves to fluctuations burden polluters. In overall. domestic wastewater treatment plant District Ulilin operate effective. stable. and feasible in support protection quality environment in a way sustainabl.